Lokalny alergiczny nieżyt nosa czy lokalne alergiczne zapalenie spojówek - Krzych-Fałta, Edyta; Wojas, Oksana (Alergologia Polska - Polish Journal of Allergology, 2023)
Differential diagnosis of the local allergic reaction is mainly based on conjunctival, nasal and bronchial provocation tests, which, in theory, may lead to further treatment. The most common local response can be observed in the nasal mucosa. In the long run, it may manifest itself by coexisting local reactions in other areas such as the eye and/or bronchial tree. In a 45-year-old patient who has been experiencing health problems typical for grass/grain allergy for nearly 10 years, two challenges were carried out, i.e. nasal and conjunctival provocation tests, and the latter elicited a highly positive response to the applied allergen compared to the intranasal route. When there are clinical discrepancies in the local allergic reaction, allergen provocation tests should be considered in the differential diagnosis and, when the results are negative, conjunctival challenge should be considered as well.